2019
DOI: 10.1071/cp18212
|View full text |Cite
|
Sign up to set email alerts
|

Importance of anther dehiscence for low-temperature tolerance in rice at the young microspore and flowering stages

Abstract: Low temperature, particularly during the reproductive stage in rice (Oryza sativa L.), leads to reduced fertility and yield and is a major constraint faced in temperate rice ecology. The floral trait anther dehiscence length has not been quantified in relation to low-temperature tolerance in rice. Two controlled-temperature glasshouse experiments evaluated 120 genotypes from BC1F6 recombinant inbred lines when exposed to low air temperature at the booting (young microspore) and flowering stages. Genotypic diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 16 publications
4
20
0
Order By: Relevance
“…Conversely in flooded conditions, spikelet sterility was significantly associated with all floral traits. The number of dehisced anthers accounted for 84% of the variation in spikelet sterility under flooded conditions, which is comparable to the findings ofSusanti et al (2019), and also was almost double that explained in the aerobic conditions. In both flooded and aerobic conditions, cold tolerant genotypes had a larger number of dehisced anthers and consequently number of pollen on stigma, contributing to reduced spikelet sterility.…”
supporting
confidence: 83%
See 4 more Smart Citations
“…Conversely in flooded conditions, spikelet sterility was significantly associated with all floral traits. The number of dehisced anthers accounted for 84% of the variation in spikelet sterility under flooded conditions, which is comparable to the findings ofSusanti et al (2019), and also was almost double that explained in the aerobic conditions. In both flooded and aerobic conditions, cold tolerant genotypes had a larger number of dehisced anthers and consequently number of pollen on stigma, contributing to reduced spikelet sterility.…”
supporting
confidence: 83%
“…The phenotypic relationship between spikelet fertility and the number of dehisced anthers previously identified by Susanti et al (2019) was also identified in both the flooded and aerobic experiment. In flooded conditions, the number of dehisced anthers explained 71% of the phenotypic variation for spikelet fertility; whereas the explained phenotypic variance was considerably less in aerobic conditions at 42%.…”
Section: Floral Traits Contributing To Spikelet Fertilitymentioning
confidence: 54%
See 3 more Smart Citations